Organic Feed Utilization of Catfish (Clarias gariepinus) Farming in Probolinggo - Maheno Sri Widodo (Journal of Innovation and Applied Technology, 2015)
Production of freshwater fish in Pro-bolinggo tend to decrease mainly due to the increase of feed cost. The purposed of this activity was dissemination of or-ganic feed technology utilization in Purut village, Lumbang and Klenang Lor village, Banyu Anyar, Probolinggo. The method of Participatory Rural Appraisal was used. This method consisted of socializa-tion, training, monitoring and evaluati-on. Utilization of organic feed was per-formed on a tarp tank with an area of 15 m2 (3 tarp pools) with stocking density (5-7 cm) of ±333  fish/m2 in each group.  Production of 1.32 tons was obtained after 75 days catfish culture with FCR value of 2.5. The profit of production by using this technology was IDR 4.290.000 per cycle. There is an increase in profit of IDR 2.190.000 (104.3%) compared to the usual culture due to a decrease of feed costs by applied this technology. Finally, the farmers can get information about the production of organic feed, can produce their own organic feed as a substitute to commercial feed and can increase their income. Keywords: aquaculture, organic food technology, tarp tank, production of catfish